SISTEM PORTOFOLIO ELEKTRONIK (E-PORTFOLIO) UNTUK MENENTUKAN BIDANG KOMPETENSI MAHASISWA - , Alva Hendi Muhammad; , Ir. Lukito Edi Nugroho, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Information in the portfolio is very valuable for the studentsâ development. In this thesis, the researcher will develop applications of electronic portfolios (eportfolio) with the ability to map the competencies of students. Student competencies are mapped according to existing information on their portfolios. This research begins by selecting a number of factors (variables) in a portfolio that can be used to assess student competency. The proposed variable further investigated whether it is feasible to be used in this study or not. There are five variables that are used in determining competency: Academic Values, Experience, Certification, Training, and Research and Publication. The results of tests conducted showed that the five variables used valid. The next step is to determine the priorities and weights of the five variables. Paired comparison technique will be used to solve these problems. This technique is used in Analytical Hierarchy Process (AHP).This decision support model will outline the problems multiple factors or a complex multi-criteria into a hierarchy. The results obtained by weighting each variable are the Academic Value (30%), Experience (14%), Certification (13%), Training (16%), Research and Publication (27%). Value of students' competencies that may be achieved is on a scale of 0-100. Then the value is compared to the scale of competence levels to determine student achievement of competencies. Final phases in this research is to develop an electronic portfolio of webbased applications that can assist users in making decisions in student competency mapping. The system will calculate the score to solve the problem accurately in a short time based on a formula that has been obtained from the previous analysis. The result is a level of competence of students who are visually displayed by the system in graphical form.